Non-cardiogenic pulmonary oedema in the course of verapamil intoxication. Issue 5 (1st September 2002) - Kartı, S Sami; Ulusoy, H; Yandı, M; Gündüz, A; Koşucu, M; Erol, K; Ratip, S
Abstract : Only three cases of non-cardiogenic pulmonary oedema secondary to high dose verapamil ingestion have been described in the literature. This report describes two girls, who developed pulmonary oedema in the course of massive dose verapamil ingestion (total of 6000 mg and 7200 mg). Left ventricule size and function was normal on transthoracic echocardiograms in both of these patients. They were treated successfully with mechanical ventilatory support. The report emphasises that this fatal complication may be seen with verapamil overdose and underlying mechanisms and therapeutic approach are discussed.